PENGELOLAAN BISNIS RUMAHAN DONAT GORENG (KASUS PADA UMKM GUSNIWATI) - Gustina, Gustina; Yenida, Yenida; Deni Wahyuni, Deni Wahyuni; Afifah, Afifah (MENARA EKONOMI, 2018)
UMKM’s Business activities are very popular nowadays like rainy season. This group has been proven to advance the country's economy through its ability to absorb labour and open new jobs. Business partners in this Community Service activity are business groups which include food clusters, namely Gusniwati's business which is engaged in the loading and selling of donuts and fried bread.The purpose of this service is to assist partners in business management and production. Through this activity, it is expected that partners can improve their business management capabilities, expand their marketing areas, improve the quality of their production, which in turn will increase partners' income and profits. This activity will be carried out in the form of business management training (packaging, business motivation marketing), and the provision of production assistance goods.